Improving the development, monitoring and reporting of stroke rehabilitation research: consensus-based core recommendations from the Stroke Recovery and Rehabilitation Roundtable (SRRR) - Walker, Marion F.; Hoffmann, Tammy C.; Brady, Marian C.; Dean, Catherine M.; Eng, Janice J.; Farrin, Amanda J.; Felix, Cynthia; Forster, Anne; Langhorne, Peter; Lynch, Elizabeth A.; Radford, Kathryn A.; Sunnerhagen, Katharina; et al. (SAGE, 2017)
Recent reviews have demonstrated that the quality of stroke rehabilitation research has continued to improve over the last four decades but despite this progress there are still many barriers in moving the field forward. Rigorous development, monitoring and complete reporting of interventions in stroke trials are essential in providing rehabilitation evidence that is robust, meaningful and implementable. An international partnership of stroke rehabilitation experts committed to develop consensus-based core recommendations with a remit of addressing the issues identified as limiting stroke rehabilitation research in the areas of developing, monitoring and reporting stroke rehabilitation interventions. Work exploring each of the three areas took place via multiple teleconferences and a two-day meeting in Philadelphia in May 2016. A total of 15 recommendations were made. To validate the need for the recommendations the group reviewed all stroke rehabilitation trials published in 2015 (n=182 papers). Our review highlighted that the majority of publications did not clearly describe how interventions were developed or monitored during the trial. In particular, under-reporting of the theoretical rationale for the intervention and the components of the intervention calls into question many interventions that have been evaluated for efficacy. More trials were found to have addressed the reporting of interventions recommendations than those related to development or monitoring. Nonetheless the majority of reporting recommendations were still not adequately described. To progress the field of stroke rehabilitation research and to ensure stroke patients receive optimal evidence based clinical care we urge the research community to endorse and adopt our recommendations.